Advances in understanding begomovirus satellites - Zhou, Xueping (Annual review of phytopathology, 2013)
Begomoviruses are numerous and geographically widespread viruses that cause devastating diseases in many crops. Monopartite begomoviruses are frequently associated with betasatellites or alphasatellites. Both betasatellite and alphasatellite DNA genomes are approximately half the size of begomovirus DNA genomes. Betasatellites are essential for induction of typical disease symptoms. The βC1 genes encoded by the betasatellites have important roles in symptom induction, in suppression of transcriptional and posttranscriptional gene silencing, and they can affect jasmonic acid responsive genes. Host plants of begomoviruses have evolved diverse innate defense mechanisms against the βC1 protein to counter these challenges. Alphasatellites have been identified mainly in monopartite begomoviruses that associate with betasatellites and have no known contributions to pathogenesis of begomovirus-betasatellite disease complexes. Applications of current molecular tools are facilitating viral diagnosis and the discovery of novel species of geminiviruses and satellite DNAs and are also advancing our understanding of the global diversity and evolution of satellite DNAs.